2011
DOI: 10.1007/s11064-011-0506-2
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxic Effect of the Complex of the Ovine Prion Protein (OvPrPC) and RNA on the Cultured Rat Cortical Neurons

Abstract: Prion diseases are conformational diseases, many factors are involved in altering the conformation of prion, such as RNA, DNA, pH, and copper etc. However the neurotoxic mechanism of prion diseases is not clear yet. The aim of this study is to investigate the effect of the nucleoprotein complex of RNA and recombinant ovine prion protein (OvPrP(C)) on the cultured rat cortical neurons in vitro. Our previous study revealed that the nucleoprotein complex (OvPrP(C)-RNA) is characterized with high β sheet conformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…12,17,18 A separate study indicates the neurotoxic effect found on the cultured rat cortical neurons of the complex of the ovine prion protein (OvPrP(C)) and RNA. 19,20 Besides, unique quadruplex structure and selective interaction of an RNA aptamer against bovine prion protein and may inhibits the prion disease propagation. 21 Understanding the processes of PrP C structural changes, viz.…”
Section: Introductionmentioning
confidence: 99%
“…12,17,18 A separate study indicates the neurotoxic effect found on the cultured rat cortical neurons of the complex of the ovine prion protein (OvPrP(C)) and RNA. 19,20 Besides, unique quadruplex structure and selective interaction of an RNA aptamer against bovine prion protein and may inhibits the prion disease propagation. 21 Understanding the processes of PrP C structural changes, viz.…”
Section: Introductionmentioning
confidence: 99%
“…11,22,28,29 The PrP−NA complex can also be toxic to cultured cells. 22,30 Knowing whether this effect is associated with specific nucleic acid sequences and/or structures would be enlightening. To answer this essential question, we started by asking whether different aggregation, stability, and toxicity effects are detected when different DNA sequences are tested.…”
mentioning
confidence: 99%
“…It has been observed that the interaction of PrP with nucleic acids is nonspecific because this protein binds several different RNA and DNA sequences in vitro. ,,, The PrP–NA complex can also be toxic to cultured cells. , Knowing whether this effect is associated with specific nucleic acid sequences and/or structures would be enlightening. To answer this essential question, we started by asking whether different aggregation, stability, and toxicity effects are detected when different DNA sequences are tested.…”
mentioning
confidence: 99%
“…After galanin treatment, cell viabilities were tested using a 3-(4,5-dimethylthiazole -2-yl)-2,5-diphenyl- tetrazolium bromide (MTT) assay [21], [22] Neuronal cell death was measured using a TdT-mediated biotin-dUTP nicked-end labeling (TUNEL) assay [23], [24], [25]. 4′-6-Diamidino-2-phenylindole (DAPI) was used to stain the nuclei of cultured cortical cells.…”
Section: Methodsmentioning
confidence: 99%